Photocatalytic Degradation of Phenol Using TiO2-Fe Under H2O2 Presence by Visible and Sunlight Irradiation - Linda J Kusumawardani; Ani Iryani (Syarif Hidayatullah State Islamic University, 2021)
Phenol is one of the essential organic pollutants released into the environment because of its high stability and toxicity. It is harmful to organisms, environment, and posing a serious threat to human health at low concentration. This research investigated the photocatalytic degradation process of phenol using a TiO2-Fe catalyst under visible light irradiation and additional H2O2. The effect of various conditions process was applied, including different catalyst doses (0.2, 0.4, 0.6, and 0.8 g/L), pH (3, 6, 8, and 11), irradiation times (60, 90, 120, 150, and 210 minutes) and the presence of H2O2. The degradation process was studied at an initial concentration of phenol 5 mg/L. This study has been decreasing phenol content (90.51%) with catalyst doses 0.6 g/ L sample solution, pH solution 11, reaction time 210 minutes and H2O2 concentration 30%. This final phenol concentration after photodegradation under halogen light was 0.18 mg/L, while sunlight irradiation was 0.11 mg/L. This result is below government regulation as per Permen LH RI No. 5/2014 i.e. 0.5 mg/L. Therefore, this process possible to remove phenol in aqueous such as industrial wastewater or other resources.